Towards a framework for analyzing determinants of performance of community health workers in malaria prevention and control: a systematic review - Helen Mwiinga Chipukuma; Joseph Mumba Zulu; Choolwe Jacobs; Gershom Chongwe; Mumbi Chola; Hikabasa Halwiindi; Jessy Zgambo; Charles Michelo (BMC, 2018)
Abstract Background Community health workers (CHWs) are an important human resource in improving coverage of and success to interventions aimed at reducing malaria incidence. Evidence suggests that the performance of CHWs in malaria programs varies in different contexts. However, comprehensive frameworks, based on systematic reviews, to guide the analysis of determinants of performance of CHWs in malaria prevention and control programs are lacking. Methods We systematically searched Google Scholar, Science Direct, and PubMed including reference lists that had English language publications. We included 16 full text articles that evaluated CHW performance in malaria control. Search terms were used and studies that had performance as an outcome of interest attributed to community-based interventions done by CHWs were included. Results Sixteen studies were included in the final review and were mostly on malaria Rapid Diagnosis and Treatment, as well as adherence to referral guidelines. Factors determining performance and effective implementation of CHW malaria programs included health system factors such as nature of training of CHWs; type of supervision including feedback process; availability of stocks, supplies, and job aids; nature of work environment and reporting systems; availability of financial resources and transport systems; types of remuneration; health staff confidence in CHWs; and workload. In addition, community dynamics such as nature of community connectedness and support from the community and utilization of services by the community also influenced performance. Furthermore, community health worker characteristics such marital status, sex, and CHW confidence levels also shaped CHW performance. Conclusions Effectively analyzing and promoting the performance of CHWs in malaria prevention and control programs may require adopting a framework that considers health systems and community factors as well as community health worker characteristics.